PWE-139 The effect of changes in care on compliance with gluten free diet in a coeliac population. (17th June 2017) - Pritchard, L; Murray, IA; Bebb, JR; Waters, C; Abdelrahim, M; Lewis, SJ
Abstract : Introduction: The recently published Quality Standards for people with coeliac disease (CD) emphasise the importance of annual review 1 . This should include review of adherence to gluten-free diet (GFD) and evaluation of symptoms. It is implied that annual review improves dietary adherence and outcomes but there is limited research in this area. We studied whether annual review was associated with improved dietary outcomes in people with CD. Method: A postal questionnaire was sent to 835 patients with CD diagnosed via positive serology and duodenal biopsy, who attended secondary care services at 2 sites (Plymouth hospitals and Royal Cornwall hospital) between 2006 and 2014. Patients were diagnosed at least 24 months earlier. We compared those with and without annual review (AR) and whether they achieved the following desirable dietary status: compliance with GFD being good or excellent; dietary calcium intake of 1000 mg/day; compliance with calcium/vitamin D supplements where appropriate being good or excellent. We assessed adherence to a GFD via a 5-point scale, dietary calcium intake (mg) as determined by a food frequency questionnaire, compliance with calcium/vitamin D supplements (if prescribed) on a 5-point scale. We also compared the number of members of Coeliac UK and those in receipt of gluten-free prescriptions (GFP). Results: A total of 516 questionnaires (61.8%) were returned. Two-thirds of patients 66% (n338) had AR. Comparing presence of AR against no AR, we found 91% achieved good/excellent adherence to GFD vs 87% (p=NS), good/excellent adherence to prescribed calcium/vitamin D supplements 72% vs 60% (p<0.01). A total of 443 respondents (86%) completed the calcium frequency questionnaire. The mean average estimated dietary calcium intake was 898 mg in those offered an AR vs. 891 mg in those that were not. Those who had AR were more likely to be members of Coeliac UK compared to those with no follow-up (56% vs 44%, p<0.05) and were more likely to have gluten free prescriptions (66% vs. 28%, p<0.05). Conclusion: Annual review for coeliac disease is associated with greater compliance with calcium/vitamin D and a non-significant increase in compliance with gluten free diet. Interestingly most coeliac patients irrespective of AR, achieved nearly 100% recommended daily intake of calcium. AR was associated with provision of prescriptions for gluten free foods which may have implications for people with CD as some clinical commissioning groups have stopped offering gluten free products on prescription. Reference: Coeliac disease: quality standard (2016) NICE quality standard QS134, statement 5 (annual review). Disclosure of Interest: None Declared